2013
DOI: 10.1111/ahg.12003
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Interleukin‐6 Gene −572 C/G Polymorphism and the Risk of Type 2 Diabetes Mellitus: A Meta‐Analysis of 11,681 Subjects

Abstract: SummaryThe association between the interleukin-6 (IL-6) gene −572 C/G (rs1800796) polymorphism and type 2 diabetes mellitus (T2DM) risk remains controversial. Thus, we performed this meta-analysis by searching PubMed, Embase, Web of Science, CBMdisc and CNKI databases until January 30, 2012. In addition, hand searching of the references of identified articles was performed. A total of 10 case-control studies including 11,681 subjects were selected to evaluate the possible association. Our results showed eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…In line to our study, Yin et al (2013) evidently found the significant association between the risk of disease and rs1800796 [OR = 1.29 (1.09-1.52), p = 0.002] in the Chinese population. It is suggested that -572 G allele increased the risk of T2D in the corresponding population (Yin et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line to our study, Yin et al (2013) evidently found the significant association between the risk of disease and rs1800796 [OR = 1.29 (1.09-1.52), p = 0.002] in the Chinese population. It is suggested that -572 G allele increased the risk of T2D in the corresponding population (Yin et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…A Natriuretic Peptide Precursor A gene (NPPA; chromosome location 1p36.21) containing rs5064 was reported to be associated with hypertension, which is involved in the predisposition of diabetes. The Interleukin-6 (IL6; chromosome location 7p21) gene was reported to be involved in insulin resistance and increased the risk of T2D development (Conen et al, 2007;Meiner et al, 2008;Yin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fernandes et al (10) reported that patients with the IL-6 (-572G/C) G allele had higher IL-6 levels than patients with the CC and CG genotypes, and the G allele was identified as a risk factor for the development of osteoarthritis. The relationship of this polymorphism with Type 2 diabetes was examined in a metaanalysis of 10 studies, which concluded that subjects with the GG genotype were at greater risk of developing the disease (27). In the present study, which examined the relationship of the IL-6 (-572G/C) polymorphism with CD, the GG genotype was determined to be a risk factor for disease development.…”
Section: Discussionmentioning
confidence: 77%
“…The tested transversion -572G→C has been associated with higher circulating IL-6 levels [19]. This SNP has also been extensively evaluated in disease-association studies, and the most consistent seems to be the association with development of type 2 diabetes mellitus [20]. Overexpression of human IL6 cDNA in MUP/hIL-6 transgenic mice resulted in retarded growth (not related to malnutrition), reduced expression and circulating levels of IGF-1 (important in development of skeletal elements) and reduced expression of the growth hormone receptor [8].…”
Section: Discussionmentioning
confidence: 99%